(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
أجريت الدراسة في محافظة اللاذقية عام 2017، بهدف تقويم طرق استخدام الأراضي الزراعية المملوكة للدولة في هذه المحافظة، وقد استخدمت المنهج الوصفي التحليلي لقياس المؤشرات والمتغيرات. بينت نتائج الدراسة، أن المساحة المستثمرة من الأراضي الزراعية المملوكة للدولة في محافظة اللاذقية قد بلغت (2980) هكتاراً من أصل (10663) هكتاراً، أي بنسبة (28%) من المساحة الإجمالية المتاحة. حيث تم الاعتماد على تأجير هذه الأراضي لصالح المزارعين، من خلال البحث الاجتماعي، كإجراء أساسي. وبلغت نسبة المساحات المؤجرة للمزارعين (27.7%) من إجمالي هذه الأراضي، في حين تم استثمار مساحة صغيرة تقدر بنحو 21 هكتاراً فقط لصالح مشروعات استثمارية (زراعية، صناعية، خدمية، سياحية)، وذلك خلال الفترة (2013-2017). غير أن المبدأ الأساسي في تأجير هذه الأراضي لصالح المزارعين يمثل إجراءً اضطرارياً لمعالجة مشكلة وضع اليد على جزء كبير منها، والذي بلغ 20.9% من المساحة الإجمالية المتاحة. إن العوائد الناتجة عن تأجير الأراضي الزراعية المملوكة للدولة قدرت بنحو 2500 ل.س/دونم، بينما ارتفعت بنحو 7-10 ضعف عند استثمار هذه الأراضي في مشاريع استثمارية خاصة، أي نحو40273 ل.س/دونم بالمتوسط. وتبلغ هذه العوائد حدها الأقصى أي نحو 100 ألف ل.س/دونم في حالة مشروعات الإنتاج الحيواني، بينما تبلغ حدها الأدنى في حالة المقالع مقدرة بنحو 16 ألف ل.س/دونم. وعند أخذ الآثار البيئية والاجتماعية المترتبة على إدارة هذه الأراضي بعين الاعتبار تبين أفضلية استثمار هذه الأراضي في مشاريع الزراعة التجارية كثيفة رأس المال مقارنة بالمشروعات الاستثمارية الأخرى. وبالتالي فإن وجود جزء كبير من الأراضي الزراعية المملوكة للدولة خارج الاستثمار أو التأجير يمثل خسارة للاقتصاد الوطني من الناحية المالية والاجتماعية، حيث يمكن أن تقدر العوائد المفقودة بنحو 3.2 مليار ل.س سنوياً. This study was conducted in Lattakia Governorate in 2017, with the aim of evaluating methods of using state-owned agricultural land (SOAL). The study methodology based on comparative analysis of many indicators to evaluate SOAL management. The results showed that the area actually invested of the total state-owned agricultural lands in Lattakia Governorate reached 2980 ha out of 10663 hectares, which is limited to 28% of the total available area. Most of this invested area was leased to the farmers through social research, as a basic way for management of SOAL lands. According to that, the area leased to farmers constituted 27.7% of the total available land, while a small area of 21 hectares was recently invested by private investment projects (agricultural, industrial, service, tourism) during the period (2013-2017). However, the fundamental principle of leasing these lands to farmers is to solve the problem of squatting on a large part of SOAL in this governorate, which amounted to about (20.9%) of the total available area. The State revenues from the leasing of state-owned agricultural land were estimated at (2500) SP / dunum. While, These revenues increased by (7-10) times when investing of these lands through private investment projects, which estimated at an average of (40273) SP / dunum. The maximum of these revenues is estimated at an average of (100) thousand SP / dunum in the case of livestock production projects, while the minimum was in the case of quarrying projects estimated at an average of (16) thousand SP / dunum. Taking into account the environmental and social impacts of SOAL management, the priority of investment in land-intensive commercial agriculture projects was better compared to other investment projects. Thus, the existence of a large part of the state-owned agricultural lands outside the investment or leasing process is a loss of the national economy financially and socially, where the lost revenues can be estimated at about 0.192-3.2 billion SP annually.